Are anti-PD1 and anti-PD-L1 alike? The non-small-cell lung cancer paradigm - Giuseppe Luigi Banna; Ornella Cantale; Melissa Bersanelli; Marzia Del Re; Alex Friedlaender; Alessio Cortellini; Alfredo Addeo (Oncology Reviews, 2020)
Anti-PD1 and anti-PD-L1 agents may have intrinsic and clinically relevant differences in the treatment of non-small cell lung cancer (NSCLC) patients. By reviewing currently available indirect evidence on these agents for NSCLC treatment, highlighting possible inter- and intra-class dissimilarities, anti-PD1 agents showed a higher response rate and a better outcome when combined with chemotherapy for the first-line treatment of patients with squamous and PD-L1 low advanced NSCLC, as compared to anti-PD-L1 agents. Conversely, anti-PD-L1 agents were responsible for less severe adverse events (AEs), particularly, immunerelated AEs. These differences could be explained by their different specific properties. Considering possible differences between anti-PD1 and anti-PD-L1 agents could be clinically relevant for treatment tailoring and inspiring new investigational approaches.